AB1212 POLYPHARMACY AND OUTPATIENT HEALTHCARE USE IN RHEUMATOID ARTHRITIS: PATTERNS AND ASSOCIATIONS. (June 2019) - Fragoulis, George E.; Psarelis, Savvas; Flourou, Christina; Tofarides, Andreas; Nikiphorou, Elena
Abstract : Background: Polypharmacy is a considerable problem in people with rheumatic diseases, including rheumatoid arthritis (RA), related amongst others to worse disease outcomes and increased cost for the health-system (1). Objectives: To assess polypharmacy in RA and usage of the health-care system (outpatient clinics) in a real-world setting. Methods: Medical records of 170 consecutive RA patients from a large outpatient service of a central hospital were retrospectively reviewed. Demographic characteristics, treatment for RA and comorbidities as well as frequency and type of visits to any outpatient services were recorded. The latter included rheumatologists, "medical specialties" doctors (general physicians, cardiologists, respiratory physicians, oncologists, dermatologists, gastroenterologists, hematologists, nephrologists and neurologists) and "surgical specialties" (general surgery, orthopedics, neurosurgery, urology, ophthalmology, ENT, maxillofacial and vascular surgery). Disease duration was defined as the time between RA diagnosis and the end of the study (May 2018). Univariable and multivariable analyses were performed (Table). Results: Data from 170 RA patients (77.1% female) with a mean±SD age of: 62.1 ± 13.7 years and disease duration: 87.8 ± 22.0 months, were recorded. The median number of non-rheumatic drugs receieved througouht disease duration was 3. Only 7% of the patients were not receiving any additional drugs, while 15.3%, 40.6% and 56.4% had received 1, 2 and 3 non-rheumatic drugs, respectively. The most commonly used non-rheumatic drugs were, anti-hypertensive, anti-osteoporotic and lipid-lowering drugs. Higher total number of drugs correlated with age of the patient and longer disease duration. Methotrexate (MTX) experienced or biologic-naïve patinets, had received a larger number of non-rheumatic drugs compared to those who had not received methotrexate or were biologic-experienced. Multivariable analysis confirmed age and exposure to methotrexate/biologics to be positively and negatively association respectively, with the number of non-rheumatic drugs received (Table). Number of visits to rheumatologists/year were: median (range) 2.9 (0.5 – 13.6). The number of visits was correlated with age of the patients, disease duration and number of non-rheumatic drugs received. Multivariable analysis, identified, disease duration, number of non-rheumatic drugs received and being MTX-naive as predictors of number of rheumatology visits (Table). Number of visits to non-rheumatologists/year were: median (range) 1.8 (0.0 – 13.7). Visits to "internal medicine" doctors were more common than in "surgical specialties" doctors (p<0.0001). Number of visits to non-rheumatologists was correlated with age, disease duration, and with the number of non-rheumatic drugs received. Multivariable analysis confirmed only the association with the total number of drugs but revealed also that being MTX-naive was also associated with more frequent visits to non-rheumatologists. Conclusion: The majority of RA patients received more than 3 (non-RA related) drugs. This increased with older age and associated with more frequent visits to rheumatology and other specialties. References: [1] Filkova M, et al. J Rheumatol. 2017 Dec;44:1786-1793 Disclosure of Interests: None declared